Processing and properties of nanocomposites - Advani, Suresh G. (World Scientific Pub., 2007)
Nanotechnology is progressing very rapidly. This book focuses on carbon nanotubes and nano clays and explore their importance and roles in composites. Hence, the chapters address processing, rheology, mechanical properties and their interaction with fiber composites. Written by renowned researchers, this book is a collection of nine chapters which embrace the role of nano particles in composites. The first three chapters focus on the use of carbon nanotubes in composites. Chapter 4 explores the interaction between traditional fiber composites and the use of nano particles in terms of benefit.